The Role of Banking and Financial Inclusion in Developing Creative Economy in Madura - Susandini, Aprilina; Hadyarti, Vidi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Indonesia has enormous potential which can be utilized by the community as capital to develop the creative economy. The three largest creative economy sectors in Indonesia are fashion, culinary and crafts. The large potential of the craft industry sector needs to be increased and it is hoped that this can also encourage another sector. One of the problems faced by creative business actors are limited capital and financing. Banking has a very important role in developing the creative economy. Madura is an island that has great potential in the field of the creative economy. However, its development requires a third party. This research aims to determine the role of regional banks in developing the creative economy in Madura. This research uses a mix method model exploratory design. This research begins with qualitative research, the results of the research will be used to develop instruments for quantitative research. The research locations are Sumenep and Pamekasan Regencies. The respondents were creative economy entrepreneurs and the BPRS Bhakti Sumekar bank.